2021
DOI: 10.1177/2397002221998227
|View full text |Cite
|
Sign up to set email alerts
|

Virtual work intensity, job satisfaction, and the mediating role of work-family balance: A study of employees in Germany and China

Abstract: This paper targets virtual work, an increasingly crucial alternative work arrangement in today’s interconnected world. Based on a survey of 308 employees working in Germany and China, we investigate the relationship between virtual work intensity, work-family balance, and job satisfaction through a mediator model. We find empirical evidence for an inverted U-shaped relationship between virtual work intensity and job satisfaction. When virtual work intensity is below a particular level, it is positively related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 136 publications
(131 reference statements)
2
19
0
Order By: Relevance
“…Furthermore, job satisfaction might at the same time be a relevant mediator in our proposed model. Since the discussion about job satisfaction’s effects is still in need of new insights, we encourage future research to follow Qiu and Dauth (2022) and determine job satisfaction’s effects through new perspectives within the virtual work context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, job satisfaction might at the same time be a relevant mediator in our proposed model. Since the discussion about job satisfaction’s effects is still in need of new insights, we encourage future research to follow Qiu and Dauth (2022) and determine job satisfaction’s effects through new perspectives within the virtual work context.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous survey research designs, we followed a convenience sampling approach (e.g. Qiu and Dauth, 2022). The survey was spread via professional networks (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The current research aimed to examine the relationship between virtual leadership and job satisfaction as a topic of interest, especially during and after the occurrence of the COVID-19 global pandemic. The conduct of this study follows the recent string of studies in the literature that address leadership and its influence in the aftermath of a global crisis (e.g., Bouwmeester and Kok, 2018 ; Qiu and Dauth, 2021 ; Zacher and Rudolph, 2021 ). As numerous industries were affected by the outbreak of the pandemic, the role of leaders in maintaining a healthy, functional, and caring environment for employees became more vivid.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual leaders can thrive in sectors that are reliant on virtual settings and are highly demanding such as the IT sector. Employees in this sector are required to have a number of skills that are technical, methodical, and analytical, which, combined with high workloads, can negatively affect employees' wellbeing (Qiu and Dauth, 2021 ; Farmanesh and Zargar, 2023 ). We observed that virtual leaders can tap into their characteristics and enhance the virtual workplace for the satisfaction of employees in the high-performing IT industry so that they are empowered to accomplish a large number of projects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation